Initial characterization of mitochondrial DNA control region haplotypes of the Antillean manatee (Trichechus manatus manatus, Sirenia:Trichechidae) in Guatemala - Mendez, Grecia; Carney, Susan; Garcia, Heidy Amelia; Quintana-Rizzo, Ester (Revista de Biología Tropical, 2023)
Introduction: Small populations are at risk of losing genetic variability much faster than large populations; this subsequently decreases their ability to adapt when facing environmental changes. A small population of the endangered Antillean manatee (Trichechus manatus manatus) has been identified in Guatemala. Objective: This study explored the genetic diversity of the Antillean manatee in Guatemala by analysing mitochondrial DNA control region haplotypes in the two most important habitats for the species, Bahía La Graciosa, a coastal bay and Bocas del Polochic, a coastal wetland, both located in the Izabal State. Methods: Genetic samples were collected using non or minimally invasive sampling techniques: scraping of epidermal tissue, collection of floating feces, and collection of tissue from carcasses. DNA extractions, DNA amplification using polymerase chain reaction (PCR), and sequencing of the control D-loop region were used to process and analyse the samples. Results: Seven mitochondrial DNA sequences were obtained from 36 samples collected (minimum of four and maximum of seven individuals). Four haplotypes were identified, A01, A03, A04, and J01. No other Central American country has reported this number of haplotypes in a manatee population, and it is the first time that haplotype A01 has been reported for the region. The Guatemalan manatee population comprises at least two genetic lineages, the Florida/Greater Antilles lineage (haplotypes A01, A03, and A04) and the Mesoamerican lineage (J01). Conclusion: Further studies, with the use of nuclear markers, are necessary to understand the population dynamics between Bahia La Graciosa and Bocas del Polochic to identify the number of management units present in the country; also, the degree of relatedness with the Belizean population needs to be established to better coordinate conservation efforts.